A Cptt‐Based Trioxo‐Rhenium Catalyst for the Deoxydehydration of Diols and Polyols. Issue 20 (25th September 2018) - Li, Jing; Lutz, Martin; Otte, Matthias; Klein Gebbink, Robertus J. M.
Abstract: Trioxo‐rhenium complexes are well known catalysts for the deoxydehydration (DODH) of vicinal diols (glycols). In this work, we report on the DODH of diols and biomass‐derived polyols using Cp tt ReO3 as a new catalyst (Cp tt =1, 3‐di‐ tert ‐butylcyclopentadienyl). The DODH reaction was optimized using 2 mol % of Cp tt ReO3 and 3‐octanol as both reductant and solvent. The Cp tt ReO3 catalyst exhibits an excellent activity for biomass‐derived polyols. Specifically, glycerol is almost quantitatively converted to allyl alcohol and mucic acid gives 75 % of muconates at 91 % conversion. In addition, the loading of Cp tt ReO3 can be reduced to 0.1 mol % to achieve a turn‐over number as high as 900 per Re when using glycerol as substrate. Examination of DODH reaction profiles by NMR spectroscopy indicates that catalysis is related to Cp‐ligand release, which raises questions on the nature of the actual catalyst. Abstract : Less is more ! Diols and biomass‐derived polyols, sustainable starting materials, were efficiency converted to very useful industrial olefin building blocks by using Cp tt ReO3 as catalyst and a secondary alcohol as reductant. Remarkably, the loading of Cp tt ReO3 can be reduced to 0.1 mol % to achieve a turn‐over number as high as 900 per Re when using glycerol as substrate.